P255 Efficacy and safety of a restrictive ferric carboxymaltose infusion strategy for iron deficiency anemia in inflammatory bowel disease patients. (27th May 2021) - Crispino, F; Grova, M; Maida, M; Renna, S; Casà, A; Rizzo, G; Macaluso, F S; Orlando, A
Abstract: Background: Iron deficiency anemia (IDA) is a common condition in patients with inflammatory bowel disease (IBD) and ferric carboxymaltose (FCM) has shown fast correction of hemoglobin (Hb) levels and good tolerability. We evaluated the response to FCM in IBD patients with IDA. The primary outcome was the assessment of the rate of response to single or multiple FCM infusions after 12 months from the first infusion. Secondary outcomes were the response to a single FCM infusion after 3 months and the assessment of FCM safety. Methods: We retrospectively included 185 consecutive patients from IBD Unit of "Villa Sofia-V. Cervello" Hospital who received at least a dose of 500 mg FCM infusion between 2015 and 2018. Complete response (CR) was defined as Hb ≥13 g/dL (men) or ≥12 g/dL (women) or Hb increase ≥2 g/dL; partial response (PR) was defined as Hb increase ≥1 and <2 g/dl, without anemia correction; response was considered either CR or PR. Failure was defined as Hb increase <1 g/dl. A univariate analysis was performed among complete responders, partial responders and failures at 3 and 12 months. Results: After 12 months the mean number of FCM infusions was 1.7 ± 1.1 and the rate of response was 139/185 (75.1%; CR: 48.6%; PR: 26.4%). Concerning our secondary endpoint, 169/185 patients received a single infusion of FCM within 3 months, and 134/169 patients (79.2%) achieved response (CR: 56.8%; PR: 22.4%). At univariate analysis low ferritin was the only variable associated with failure at 12 months (p < 0.003). No adverse events were reported. Conclusion: A restrictive FCM infusion strategy is effective in most IBD patients with IDA. Interestingly, no association was found with Hb and weight at baseline, so further studies are needed to assess their effective role in deciding dosage of FCM.